2016
DOI: 10.21037/qims.2016.07.08
|View full text |Cite
|
Sign up to set email alerts
|

Hirayama’s disease: an Italian single center experience and review of the literature

Abstract: HD is a rare entity and a self-limited condition, but it has to be early differentiated from other diseases that may determine myelopathy and amyotrophy to establish a correct therapy and limit arm impairment. MRI is very important to confirm the clinical suspect of HD and a standardized MRI protocol using axial and sagittal images in both neutral and flexing position is needed, in order to diagnose and follow up affected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 48 publications
0
21
0
3
Order By: Relevance
“…[14][15][16][17] Some authors also proposed atopy and elevated serum immunoglobulin E levels as participating factors. 18 Tanaka et al 19 observed the intrathecal upregulation of proinflammatory T-helper-1 cytokines/ chemokines, such as interferon-␥ and macrophage inflammatory proteins-1 ␤ chemokine, in the CSF of patients with HD, indicating the possible involvement of intrathecal immunologic processes in this condition. In 2010, Ciceri et al 20 proposed that venous congestion in flexion might play an additional role in determining spinal cord ischemic changes.…”
Section: Discussionmentioning
confidence: 99%
“…[14][15][16][17] Some authors also proposed atopy and elevated serum immunoglobulin E levels as participating factors. 18 Tanaka et al 19 observed the intrathecal upregulation of proinflammatory T-helper-1 cytokines/ chemokines, such as interferon-␥ and macrophage inflammatory proteins-1 ␤ chemokine, in the CSF of patients with HD, indicating the possible involvement of intrathecal immunologic processes in this condition. In 2010, Ciceri et al 20 proposed that venous congestion in flexion might play an additional role in determining spinal cord ischemic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Vitale et al [ 17 ] suggested an MRI protocol including: sagittal T1-weighted and T2-weighted sequences and axial T2 or T2*-weighted sequence in neutral position; sagittal T2-weighted sequences and axial T2 or T2*-weighted sequence in a neck-flexion of 25–35 degrees in addition to sagittal T1-weighted sequences in neck-flexion before and after gadolinium intravenous administration. Snake-eyes appearance, a radiological finding described as a symmetrical bilateral small high-signal-intensity lesion on axial T2-weighted MRI, appears during the late stage of “Hirayama disease” and is proposed as an indicator of irreversible damage and poor prognosis [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fusion procedures, anterior or posterior, arrest segmental movement, and prevent the dural migration and cord compression during flexion. Duraplasty after laminectomy or laminoplasty, 21,[36][37][38][39][40] on the other hand, directly addresses the pathology of the tight dural canal. An added advantage of a posterior procedure is that it also addresses the flexion-induced dilatation of the epidural venous plexus seen in HD.…”
Section: Surgical Options In Hdmentioning
confidence: 99%
“…A literature search revealed that while over 300 cases of HD 6,8,26 were managed with anterior or posterior fusion, only 16 patients were treated with duraplasty without fusion (►Table 5). 16,21,[36][37][38][39][40] Ours is the first large series that critically evaluates CD as a surgical option in HD.…”
Section: Selection Of Surgical Proceduresmentioning
confidence: 99%